O ser e o tornar-se docente em alternância: memórias do presente, passado e futuro - Oliveira, Grasiela Lima de (2018)
This dissertation presents the (auto)biographical narratives of four monitors and a monitor of the area of natural sciences. Through his memories, trajectories and life histories we investigate his being and become an alternating teacher, understood both as a field of study and as being able to alternate between different universes. Therefore, we have the objective of knowing the alternating life of the natural science monitors in the EFAs of the REFAISA network, during the construction of their being and becoming a professional of the field, based on their trajectories / stories of life. It is a qualitative research, based on the concepts of memory, (auto) biography, life history and narratives. Semi-structured interviews were carried out to collect data. For the analysis of the data generated, we tried to appropriate the idea of experience, Jorge Larrosa and Professorality, by Marcos Villela Pereira, and also wanted to listen to our participants, so we felt obliged to work all issues that somehow affect them. From the analysis of the data, we can conclude that much of this being and becoming a teacher is permeated by experiences that are touching him along his trajectories, whether personal or professional, which leads to the construction of a qualityality, which is the difference in itself, and even when and I want to follow models, to be equal to others, I can not, because I build myself the teacher / monitor that I can, and this achievement is linked to what affects me, what happens to me In the case of EFAs feel more comfortable as a teacher or monitor is connected to the trajectory, a history built in contact with the family, in school as a student and then as a teacher, in their initial and continued formation. Our life is an eternal game, where we are influenced by ideas, brands that we carry from our lives and often we want to be equal to people who are considered important, however, our differences project us to other ways, to be unique, to change, with that our life is unstable and as a teacher we need to eternally rebuild ourselves.